Persisting non-albicans candidemia in low birth weight neonates in a tertiary care hospital, Jammu and Kashmir - Jahan, Tabindah; Farhana, Anjum; Nargis, Sabah (International Journal of Research in Medical Sciences, 2023)
Background: Neonatal candidemia is among the leading causes of mortality in neonatal intensive care units of the developing countries like India. This work aimed at determining the prevalence of candidemia, spectrum of disease, risk factors and the antifungal susceptibility in low birth weight neonates in neonatal intensive care unit (NICU)’s at a tertiary care level. Methods: This was a prospective cross-sectional study of blood culture positive candidemia cases in neonates admitted to the neonatal intensive care unit of tertiary care hospital, SMHS, Jammu and Kashmir, India, between July 2021 to December 2022. All neonates with a clinical suspicion of candidemia with a positive blood culture (BacT alert) were identified. Patient demographics, clinical details, neonatal risk factors, and laboratory data and antifungal susceptibilities (using VITEK 2 compact system) were recorded and analyzed. Results: A total of 680 neonatal blood culture samples were collected from NICU’s, out of which 88 (12.94%) developed candidemia. Low birth weight (33.33%), indwelling catheters (31.52%), prematurity (31.31%) and prolonged use of antibiotics were important risk factors. The commonest clinical manifestation was feed intolerance 66.1% and respiratory distress 62.2%. Non-albicans candida was seen in majority cases 86.36% with Candida krusei 77.27%. All the Candida spp. showed 100% sensitivity to voriconazole and caspofugin followed by amphotericin B, fluconazole and micafugin. Conclusions: In this study, we focussed on determining the prevalence of candidemia in low birth weight neonates. The persistently emerging non-albicans Candida particularly Candida krusei has emerged as a big concern and needs attention for its prevention and treatment to minimize the morbidity and mortality rate.